2019
DOI: 10.1186/s40359-019-0324-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical activity levels and symptoms of depression, anxiety and stress in individuals with alopecia Areata

Abstract: Background Alopecia Areata (AA) is an autoimmune condition that is characterised by non-scarring hair loss. Its aesthetic repercussions can lead to profound changes in psychological well-being. Although physical activity (PA) has been associated with better mental health outcomes in diverse populations, the association in individuals with AA has not been established. The aim of this study was to examine the associations between PA and mental health outcomes in individuals with AA to inform interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…Physical activity participation was found to be positively associated with HRQoL and negatively related to perceived stress. These statistics are supported by other similar studies where physically active people reported significantly higher HRQoL and lower levels of perceived stress [11,12]. Regular exercise has also been found to have the ability to reduce the severity of infections when people continued to remain active during the SARs period and they were more likely to survive compared with people who were more sedentary [34,35].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Physical activity participation was found to be positively associated with HRQoL and negatively related to perceived stress. These statistics are supported by other similar studies where physically active people reported significantly higher HRQoL and lower levels of perceived stress [11,12]. Regular exercise has also been found to have the ability to reduce the severity of infections when people continued to remain active during the SARs period and they were more likely to survive compared with people who were more sedentary [34,35].…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, researchers have demonstrated that there was a decrease in the level of outdoor physical activity and an increase in sedentary time during the COVID-19 pandemic as a result of home confinement [3,10]. A reduction in physical activity participation is known to contribute to stress levels, which is strongly associated with HRQoL [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There was statistically significant difference between patients and controls (p=0.003). Many studies [14,15] which measured the frequency and number of stressful life events occurring over a specified period among alopecia areata suggested that such patients endured a significantly higher number of stressful life events than do controls suggesting that psychological distress may have contributed to the onset of alopecia areata.…”
Section: Discussionmentioning
confidence: 99%
“…Personal problems were more noted by women (p=0.050) and financial ones were more cited by men (p=0.003). Potential stressful situations for alopecia areata were personal problems and family problems, particularly in women [14]. Other studies [16][17][18] showed that many patients experienced the death of a close friend or family member and separation.…”
Section: Discussionmentioning
confidence: 99%
“…As a hair disease, alopecia has a great influence on the mental and psychological health of patients (Rajoo et al. 2019 ). Currently, the prevention and treatment of alopecia mainly includes surgical treatment and/or drug treatment.…”
Section: Current Use Of Dop In Hair Growth Promotingmentioning
confidence: 99%